Study on Clinical Data and Molecular Analysis of Admitted Colorectal Cancer Patients in Chittagong Medical College Hospital (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Cancer is an emerging socio-economic burden of the world. Colorectal cancer exerts significant morbidities and mortalities all around the globe. In Bangladesh detailed data on the demographic status and clinic-pathological information of CRC patients are not well documented. The aim of our study is to evaluate the different socio-economic details (i.e. Age, sex, income, personal risk factors, etc.) histo-pathological variants of CRC and mutated gene on molecular analysis for better cancer therapeutics in the admitted patients of colorectal cancer in Chittagong Medical College Hospital.Materials and methods A retrospective, single center, observational study was performed in the Department of General Surgery, Chittagong Medical College Hospital from July 2023 to December 2023. All the patients admitted with colorectal cancer was included (n=120) in the study. A prescribed data collection sheet was applied to gather information. Sixty representative tissues from resected specimen were sent for molecular analysis to detect mutated gene in the Molecular Biology Department of University of Chittagong. Results were compiled at the end of the study.Results: The age of the patients’ ranges from 15 to 75 years with peak age between 36-45 years (45%) and male preponderance (65%). About 52% patients were smoker and 60% were hailing from low socio-economic condition.55% patients presented with rectal and rectosigmoid junction cancer and 80% were histopathologically diagnosed as adenocarcinoma. About 42% patients underwent Abdomino-Perineal Excision of Rectum (APER) and 25% patients needed diversion stoma(ileostomy or colostomy). All the patients presented with APC gene mutation and 53% presented with k-ras mutation.Conclusion: Middle aged males hailing from low socioeconomic condition are affected by CRC. Rectum and recto-sigmoid junction tumour are common and molecular analysis of CRC patients established the genetic basis of the cancer biology which can be implementable in the cancer therapeutics.JCMCTA 2024 ; 35 (1) : 139-141